ALGORITHM FOR DETERMINING THE INITIAL COORDINATES OF A ROBOTIC UNMANNED AERIAL VEHICLES UNDER NAVIGATION FIELD DISTORTION - G. I. Linets; S. V. Melnikov; O. Shayakhmetov; A. Isaev; M. A. Isaev (Современная наука и инновации)
Robotic unmanned aerial vehicles (RBLA) are widely used in the military, mainly in intelligence. Large vehicles can be equipped with weapons and conduct combat operations.